Diagnostic Accuracy of the Optical Coherence Tomography in Assessing Glaucoma Among Filipinos. Part 1: Categorical Outcomes Base on a Normative Database - Noel de Jesus Atienza, MD, MSc; Joseph Anthony Tumbocon, MD (Philippine Journal of Ophthalmology)
Objective: To determine the accuracy of the optic nerve head (ONH) and retinal nerve fiber layer (RNFL) parameters using the Stratus OCT in diagnosing glaucoma among Filipino patients and to determine the validity of the OCT measurements compared with a reference standard.